2022
DOI: 10.3389/fimmu.2022.768811
|View full text |Cite
|
Sign up to set email alerts
|

Potential Determinants for Radiation-Induced Lymphopenia in Patients With Breast Cancer Using Interpretable Machine Learning Approach

Abstract: Radiation-induced lymphopenia is known for its survival significance in patients with breast cancer treated with radiation therapy. This study aimed to evaluate the impact of radiotherapy on lymphocytes by applying machine learning strategies. We used Extreme Gradient Boosting (XGboost) to predict the event of lymphopenia (grade≥1) and conduced an independent validation. Then, we induced feature attribution analysis (Shapley additive explanation, SHAP) in explaining the XGboost models to explore the directiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Recently, a group at the University of Hong Kong published several studies that highlighted predictive factors of lymphocytopenia, including the use of VMAT, EDIC, and chemotherapy 6,8,9 . They also explored the potential determinants of radiation‐induced lymphopenia using a machine learning approach 10 . The present study analyzed standard clinical and treatment‐related factors to identify the predictive factors for lymphocytopenia.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Recently, a group at the University of Hong Kong published several studies that highlighted predictive factors of lymphocytopenia, including the use of VMAT, EDIC, and chemotherapy 6,8,9 . They also explored the potential determinants of radiation‐induced lymphopenia using a machine learning approach 10 . The present study analyzed standard clinical and treatment‐related factors to identify the predictive factors for lymphocytopenia.…”
Section: Discussionmentioning
confidence: 59%
“…6,8,9 They also explored the potential determinants of radiation-induced lymphopenia using a machine learning approach. 10 The present study analyzed standard clinical and treatment-related factors to identify the predictive factors for lymphocytopenia. Regression analysis revealed that regional lymph node irradiation and a lower lymphocyte count of < 1000/µL before radiotherapy were associated with severe lymphocytopenia in patients treated with and without chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organ transplant recipients accepting an organ from a cancer survivor donor may develop malignancy because exposure to the immunosuppressant drugs that prevent organ rejection allows hidden latent metastases (transplanted with the organ) to spring to life [55]. Notably, some types of cancer treatment, such as chemotherapy, radiation, and the combination of chemotherapy and immunotherapy can also cause severe lymphopenia, which is correlated with reduced survival [50,56,57].…”
Section: Introductionmentioning
confidence: 99%